A relação com o Saber do diretor escolar e os sentidos do aprender na escola - Ramos, Renata Pierini (Universidade Federal de São Carlos, 2026)
This study aims to analyze what knowledge, from the perspective of school principals, is mobilized and how it guides their decisions and practices in monitoring teaching processes, considering the multiple administrative, political, and pedagogical demands that strain the exercise of their role. The research, exploratory in nature and with a qualitative approach, was developed as a case study in a Municipal Education Department in a city in the interior of the State of São Paulo. The investigation sought to understand what knowledge is mobilized by school principals and how this knowledge guides their decisions and practices, as a relevant part of pedagogical management, in monitoring teaching processes, considering the multiple administrative, political, and pedagogical demands that strain the exercise of their role in the daily school routine. The hypothesis was that the multiple demands placed on school administrators limit the systematic monitoring of the teaching process, which is not a priority, favoring the prevalence of practical knowledge, from the perspective of the Relationship with Knowledge, such as participation in class/year council meetings and the analysis of indicators from large-scale assessments, to the detriment of continuous monitoring. The methodological procedures adopted included document analysis and focus groups. The research was also supported by a mapping of academic productions on school management and teaching, contributing to the construction of the theoretical framework and to the understanding of the state of knowledge on the investigated theme. The data were organized into constellations based on Charlot's theory: (1) Epistemic Dimension: of possession, mastery and self-constitution; (2) Social Dimension: of the social being – my place of speech; and (3) Identity Dimension: of the being that I am – the identity of the subject. The analysis of these dimensions made it possible to understand the knowledge mobilized by the director in pedagogical management, expressed in direct and indirect interventions in the teaching processes. The results show that, although not systematically, the professionals investigated demonstrate commitment to creating favorable conditions for achieving the school's educational objectives. This finding is partly related to the hierarchical structure of the management team promoted by the investigated Department of Education, which favors the distribution of responsibilities and reduces possible gaps in monitoring learning. In light of the Relationship with Knowledge (RcS), it was found that the knowledge mobilized by the managers goes beyond technical skills, involving conceptions of education, professional trajectories, belonging, and positions regarding the concrete working conditions. Thus, pedagogical leadership is built not only by complying with legal prescriptions, but also by the daily construction of meanings and practices focused on the centrality of the teaching and learning process. This research reinforces findings already established in the literature on school management, highlighting that Brazilian school principals face feelings of isolation and intense bureaucratic overload. Furthermore, it indicates that the principal's desire and willingness to monitor learning processes are decisive factors for this monitoring to occur consistently and meaningfully.
The school principal's relationship with Knowledge and the meanings of learning at school
Keywords: Diretor de Escola; Processo de Ensinar e Aprender; Gestão Pedagógica; School principal; Teaching and Learning Process; Pedagogical Management; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade